TINJAUAN HUKUM FUNGSI YAYASAN YANG DIDIRIKAN OLEH PERSEROAN TERBATAS - MONA WINATA SIAHAAN; BISMAR NASUTION; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
The Institution of foundation has been widely recognized and was born in Indonesia since the days of the Dutch Indies government until Indonesia. Prior to the birth of Legislation No.16 of 2001 on the foundation has been no legal provision that regulates regarding the foundation. Up to the birth of the legislation No.16 of 2001 jo. Legislation 28 of 2004 on the foundation, in Article 1 item 1 is mentioned understanding the foundation is a legal entity which consists of the wealth were separated and destined to achieve certain goals in the social, religious and humanitarian who do not have a common member. The issues raised in this thesis is how to arrangement the foundation based on the Foundation of the legislation No. 16 of 2001 jo. The legislation No. 28 of 2004, is how the legal relationship among the limited liability company with the foundation established by the limited liability company and how the function of foundation established by the limited liability company. The research method used in writing this thesis is normative or the law method is also called the method of literature. Normative legal research is the legal research with cultivate and using the secondary data. The results of this research shows clearly that foundation established by the limited liability company as the founder of a foundation separates the beginning a wealth and established the foundation as a legal entity institution. The function of a foundation established by the limited liability company remained perform its functions in the social field, religious and humanitarian and a foundation purpose as provided by the Legislation of the foundation. Kata Kunci : Fungsi, Yayasan, Perseoan Terbatas.